THE CONSIDERATIONS OF DESIGNING MODERN METAL FURNITURE SUPPLEMENTS FOR HOTEL RESTAURANTS, BENEFITTING FROM ISLAMIC ART (WITH THE APPLICATION AT THE RADISSON BLUE HOTEL, JIZAN CITY) - Sadaa Hussein Abdullah Khobrani, Dr. Abdelrahman Abouzaid Mohamed Abouzaid (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The study is concerned with investigating elements and decorations of Islamic art products as a source and reference for inspiration and benefitting from its shape and decoration. The study aims at developing considerations for the design of metal supplements for hotel restaurants and the application at Radisson Blue Restaurant and Hotel at Jazan city. The study has used the historical, the descriptive, the analytical and the applied methods for the inference and development of these considerations. Some of the most important of these considerations are to benefit from the features of Islamic art such as avoiding space, to work on the occupying adornments, its intensity and communication to cover all or part of the requested space. Some other considerations are treating Islamic arts as decorative arts, away from protrusions and propositions; avoiding splashing into covering the spaces with flat decorations; compensating the shortage in coloring and gilding, being away from accuracy in nature representation, adoption of repetition in decorative topics, considering illustrations; and making use of polygons. The study recommends that designers should benefit from and take advantage of elements, decorations and features of the Islamic art.